Sarcoma esophagus: A case report and review of literature (Indian Journal of Case Reports, 2020)
Synovial sarcoma (SS) is an uncommon mesenchymal malignant neoplasm that occurs mainly in extremities. Sarcoma of the esophagus is a rare neoplasm and comprises 0.1–1.5% of all esophageal tumors. Only a few cases have been reported from the Indian context. We report a case of SS occurring in the esophagus of a 35-year-old male and managed with radical radiotherapy alone. We also want to highlight the histopathological and immunohistochemistry profile which aid in its accurate diagnosis. Molecular testing for SS18-SSX was done for confirmation.